PENGETAHUAN DAN PERSEPSI APOTEKER TERHADAP SISTEM PELAPORAN MONITORING EFEK SAMPING OBAT (MESO) DI APOTEK WILAYAH KOTA YOGYAKARTA - Sarah Ulfah; Hendy Ristiono; Dyah A Perwitasari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
The importance of pharmacovigilance activity is the Adverse Drug Reaction (ADR) reporting system. Many pharmacists who do not report ADR incident and number of ADR indicated that more knowledge and good perception of ADR is needed. This study was aimed at investigating the knowledge and perception of pharmacists towards the ADR reporting system of Community Pharmacists in Yogyakarta City, Indonesia. Cross sectional study design was conducted to community pharmacists (n=275) in Yogyakarta City, Indonesia on the period of November 2016 to March 2017. All data were analysed by Statistical Package for Social Sciences (SPSS) software V.16.0. Results were reported as frequency, and we used cross tabulation. The questionnaire consisted of questions about the sociodemographic characteristics of the Pharmacists. Furthermore, questionnaire with nine and eight points for assessing knowledge and perception about ADR Reporting System in Indonesia was used. The response rate of community pharmacists reached 36% (n = 100). A majority of the respondent was female (81%) and respondents of age group 20–30 years were predominantly (55%). Most of the respondents was graduated as pharmacist (85%), in the graduation year of 2010-2016 (55%). Most of the pharmacist had 1-5 years of work experience (44%) and never get pharmacovigilance training (86%). Most of the pharmacists had fair knowledge ( 40%) and fair perception (65%) towards the ADR reporting system. Pharmacovigilance training and last education of community pharmacists could influence the pharmacists’ knowledge (p: 0.00 and 0.013, respectively). Moreover, there was no significant association between pharmacists’ knowledge and perception (p > 0.496).